1992
DOI: 10.1203/00006450-199207000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxemia and Reoxygenation with 21% or 100% Oxygen in Newborn Pigs: Changes in Blood Pressure, Base Deficit, and Hypoxanthine and Brain Morphology

Abstract: ABSTRACT. To study whether room air is as effective as 100% 0 2 in resuscitation after hypoxia, hypoxemia (Pao2 2.3-4.3 kPa) was induced in newborn pigs (2-5 d old) by ventilation with 8% O2 in nitrogen. When systolic blood pressure had fallen to 20 mm Hg, animals were randomly reoxygenated with either 21% Oz (group 1, n = 9) or 100% 0 2 (group 2, n = 11) for 20 min followed by 21% O2 in both groups. Controls (group 3, n = 5) were ventilated with 21% 0 2 throughout the experiment. Base deficit peaked at 31 f 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
0
3

Year Published

1994
1994
2010
2010

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(51 citation statements)
references
References 15 publications
7
41
0
3
Order By: Relevance
“…All values are given as mean Ϯ SEM. 788 between 21 and 100% oxygen even 4 d after hypoxia (54). Despite this, our study indicates the importance of adjusting down the oxygen level during resuscitation after global hypoxia.…”
Section: Discussionmentioning
confidence: 59%
“…All values are given as mean Ϯ SEM. 788 between 21 and 100% oxygen even 4 d after hypoxia (54). Despite this, our study indicates the importance of adjusting down the oxygen level during resuscitation after global hypoxia.…”
Section: Discussionmentioning
confidence: 59%
“…In the presence of elevated levels of cerebral hypoxanthine and xanthine, a large amount of oxygen administered during resuscitation after peripartal asphyxia may provide adverse effects. In newborn pigs, resuscitation after asphyxia with 100% oxygen was not shown to be beneficial compared with resuscitation with 21% oxygen (20). It may therefore be worthwhile to consider using 21% instead of 100% oxygen during resuscitation after peripartal asphyxia.…”
Section: --30mentioning
confidence: 99%
“…In this and a series of subsequent experiments, we confirmed that 21% oxygen is as efficient as 100% oxygen for resuscitation. [10][11][12][13][14][15][16] The findings in the newborn piglet were consistent, and I realized that the time had come to test our hypothesis in a clinical study. Siddarth Ramji in New Delhi immediately agreed to participate, and the pilot clinical trial was carried out in India, enrolling 84 newborn infants randomized to room air or 100% oxygen resuscitation.…”
Section: Discovery Through a Failurementioning
confidence: 73%